Heat shrinkable multilayer film
The heat-shrinkable multilayer film with polyester and polystyrene layers addresses surface defects and ink omission by enhancing detection accuracy and surface smoothness, ensuring high-quality printing and film integrity.
Patent Information
- Application Number
- JP2023199789
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2038-09-28
AI Technical Summary
Conventional heat-shrinkable films suffer from defects such as scratches and foreign objects on the surface, and ink omission during printing due to uneven surfaces caused by crosslinked gel, leading to interference fringes that obscure defects and affect printing quality.
A heat-shrinkable multilayer film with front and back layers made of polyester resin and an intermediate layer of polystyrene resin, with a retardation of 0.1 to 2900 nm, designed to improve defect detection accuracy and prevent ink omission by enhancing surface smoothness and clarity.
The multilayer film effectively detects surface defects and prevents ink omission by ensuring even surface quality, allowing for precise printing and improved film integrity.
Smart Images

Figure 0007601994000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat-shrinkable multilayer film that allows easy detection of defects such as scratches and foreign matter present on the film surface and can prevent defects such as ink loss after printing. [Background technology]
[0002] 2. Description of the Related Art Heat-shrinkable labels based on heat-shrinkable resin films are attached to many containers such as plastic bottles and metal cans. Heat shrinkable labels have a printing layer for applying characters and designs such as product name, logo mark, manufacturer name, etc. to distinguish the product from other companies' products. In order to differentiate from other companies and to increase appeal to consumers, the number of detailed designs is increasing. Therefore, heat shrinkable resin films are required to have an appropriate surface shape.
[0003] In polystyrene-based heat-shrinkable films, whose main material is styrene-butadiene block copolymer (SBS), the butadiene in the butadiene block copolymer undergoes thermal crosslinking during heat-melt processing, generating crosslinked gels (fish eyes). When printing on the film, problems occur in which the ink in those areas comes off due to the unevenness created by the crosslinked gel migrating to the surface, especially during stretching. In response to this, Patent Document 1 discloses a heat-shrinkable film that can be used for applications such as shrink packaging, shrink bundling packaging, and shrink labels, and that has little crosslinked gel (fish eyes).
[0004] Furthermore, in order to accommodate increasingly diverse printing designs, further improvements in the surface shape of heat-shrinkable films are desired, and heat-shrinkable films are monitored for defects (foreign objects such as fish eyes) that occur during production using defect detectors, and any gels or other particles that occur are removed before the film is shipped.
[0005] Methods for inspecting for defects in heat-shrinkable film include using a white fluorescent lamp as a light source, shining this through a polarizing filter from behind the heat-shrinkable film, taking an image with a CCD camera equipped with a polarizing filter placed on the opposite side, and using image processing to detect light leakage (transmission) from the defects to determine whether the film is good or bad; and using infrared light as a light source, similarly taking an image with a CCD camera equipped with a visible light cut filter, and processing the image to detect defects.
[0006] However, with conventional heat-shrinkable films, interference fringes appear when images are captured with a CCD camera equipped with a polarizing filter, which can lead to defects being overlooked, resulting in problems such as ink loss during printing. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2005-28736 A Summary of the Invention [Problem to be solved by the invention]
[0008] In view of the above-mentioned current situation, the present invention aims to provide a heat-shrinkable multilayer film that allows easy detection of defects such as scratches and foreign matter present on the film surface and prevents defects such as ink bleeding after printing. [Means for solving the problem]
[0009] The present invention is a heat-shrinkable multilayer film having front and back layers containing a polyester resin and an intermediate layer containing a polystyrene resin, the heat-shrinkable multilayer film having a retardation (Re) of 0.1 to 2900 nm. The present invention will be described in detail below.
[0010] The inventors discovered that in a heat-shrinkable multilayer film, by using a polyester-based resin as the resin constituting the front and back layers and a polystyrene-based resin as the resin constituting the intermediate layer, and further by setting the retardation within a predetermined range, the accuracy of defect detection can be improved, and thus completed the present invention.
[0011] The heat-shrinkable multilayer film of the present invention has a structure in which a front and back layer and an intermediate layer are laminated. In this specification, the term "front and back layers" refers to both the front and back layers. Thus, the heat-shrinkable multilayer film of the present invention has a structure in which the intermediate layer is sandwiched between the front and back layers.
[0012] (Front and back layers) The front and back layers each contain a polyester resin. The polyester resin constituting the front and back layers can be obtained by polycondensation of a dicarboxylic acid and a diol. The dicarboxylic acid is not particularly limited, and examples thereof include o-phthalic acid, terephthalic acid, isophthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, octyl succinic acid, cyclohexanedicarboxylic acid, naphthalenedicarboxylic acid, fumaric acid, maleic acid, itaconic acid, decamethylene carboxylic acid, anhydrides thereof, and lower alkyl esters thereof. The diol is not particularly limited, and examples thereof include aliphatic diols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, diethylene glycol, 1,5-pentanediol, 1,6-hexanediol, dipropylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propanediol, 1,3-butanediol, 2,3-butanediol, neopentyl glycol (2,2-dimethylpropane-1,3-diol), 1,2-hexanediol, 2,5-hexanediol, 2-methyl-2,4-pentanediol, 3-methyl-1,3-pentanediol, and 2-ethyl-1,3-hexanediol; and alicyclic diols such as 2,2-bis(4-hydroxycyclohexyl)propane, alkylene oxide adducts of 2,2-bis(4-hydroxycyclohexyl)propane, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol.
[0013] Among the polyester-based resins, those containing a component derived from terephthalic acid as a dicarboxylic acid component and containing components derived from ethylene glycol and 1,4-cyclohexanedimethanol as diol components are preferred. By using such a polyester-based resin, it is possible to impart particularly high heat resistance and solvent resistance to the heat-shrinkable multilayer film of the present invention.
[0014] In the polyester resin, the content of the component derived from terephthalic acid in 100 mol % of the dicarboxylic acid component is preferably 60 mol %, more preferably 65 mol %, and more preferably 100 mol %, more preferably 95 mol %. In the polyester resin, the content of the component derived from isophthalic acid in 100 mol % of the dicarboxylic acid component is preferably 0 mol %, more preferably 5 mol %, and more preferably 45 mol %, more preferably 40 mol %.
[0015] In the polyester resin, the content of the component derived from ethylene glycol in 100 mol % of the diol component is preferably 0 mol %, more preferably 60 mol %, and more preferably 100 mol %, more preferably 95 mol %. In the polyester resin, the content of the component derived from 1,4-cyclohexanedimethanol in 100 mol % of the diol component is preferably 0 mol %, more preferably 10 mol %, and more preferably 40 mol %, more preferably 35 mol %. In the polyester resin, the content of the component derived from diethylene glycol in 100 mol % of the diol component is preferably 0 mol %, more preferably 2 mol %, and more preferably 30 mol %, more preferably 25 mol %. In the polyester resin, the content of the component derived from butanediol in 100 mol % of the diol component is preferably 0 mol %, more preferably 5 mol %, and more preferably 100 mol %, more preferably 95 mol %. As the polyester resin constituting the front and back layers, a polyester resin having the above-mentioned composition may be used alone, or two or more kinds of polyester resins having the above-mentioned composition may be used in combination.
[0016] It is preferable to use the polyester resin having a relatively low crystalline melting temperature or no crystalline melting temperature. In the production of heat-shrinkable multilayer films, trimmed pieces or recycled films from stretching may be reused as return materials. Usually, such return materials are mixed with polystyrene resins as raw materials for the intermediate layer, but since polystyrene resins and polyester resins have different properties such as melting points, when film molding is performed at a temperature suitable for molding polystyrene resins, the polyester resins may be extruded in an unmelted state. However, by using a polyester resin having a relatively low crystalline melting temperature or no crystalline melting temperature, it is possible to prevent the unmelted polyester resin from being generated as a foreign matter in the molded film.
[0017] The front and back layers may contain additives such as antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, antiblocking agents, flame retardants, antibacterial agents, fluorescent brightening agents, and colorants, as necessary.
[0018] (Middle class) The heat-shrinkable multilayer film of the present invention contains the above-mentioned intermediate layer. The intermediate layer contains a polystyrene resin. Examples of the polystyrene resin include aromatic vinyl hydrocarbon-conjugated diene copolymers, mixed resins of aromatic vinyl hydrocarbon-conjugated diene copolymers and aromatic vinyl hydrocarbon-aliphatic unsaturated carboxylic acid ester copolymers, rubber-modified impact-resistant polystyrene, etc. By using the polystyrene resins, the heat-shrinkable multilayer film of the present invention can start shrinking at a low temperature and has high shrinkability.
[0019] In this specification, the aromatic vinyl hydrocarbon-conjugated diene copolymer refers to a copolymer containing a component derived from an aromatic vinyl hydrocarbon and a component derived from a conjugated diene. The aromatic vinyl hydrocarbon is not particularly limited, and examples thereof include styrene, o-methylstyrene, and p-methylstyrene. These may be used alone or in combination of two or more. The conjugated diene is not particularly limited, and examples thereof include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, and 1,3-hexadiene. These may be used alone or in combination of two or more.
[0020] The aromatic vinyl hydrocarbon-conjugated diene copolymer preferably contains a styrene-butadiene copolymer (SBS resin) because of its excellent heat shrinkability. In order to produce a heat shrinkable multilayer film with fewer fisheyes, the aromatic vinyl hydrocarbon-conjugated diene copolymer preferably contains a styrene-isoprene copolymer (SIS resin) using 2-methyl-1,3-butadiene (isoprene) as the conjugated diene, a styrene-isoprene-butadiene copolymer (SIBS), or the like. The aromatic vinyl hydrocarbon-conjugated diene copolymer may contain any one of SBS resin, SIS resin and SIBS resin alone or a combination of two or more. When two or more of SBS resin, SIS resin and SIBS resin are used, the resins may be dry blended, or a compound resin may be used in which the resins are kneaded in a specific composition using an extruder and pelletized.
[0021] When the aromatic vinyl hydrocarbon-conjugated diene copolymer contains SBS resin, SIS resin and SIBS resin alone or in combination, a heat-shrinkable multilayer film having particularly excellent heat shrinkability can be obtained, and therefore it is preferable that the styrene content is 65 to 90% by weight and the conjugated diene content is 10 to 35% by weight relative to 100% by weight of the aromatic vinyl hydrocarbon-conjugated diene copolymer. If the styrene content is more than 90% by weight or the conjugated diene content is less than 10% by weight, the heat-shrinkable multilayer film may be easily cut when tension is applied thereto, or may unexpectedly break during processing such as printing. If the styrene content is less than 65% by weight or the conjugated diene content is more than 35% by weight, foreign matter such as gel may be easily generated during molding processing, or the heat-shrinkable multilayer film may become weak, resulting in poor handling properties.
[0022] The Vicat softening temperature of the polystyrene resin is preferably 60°C as a lower limit and 85°C as an upper limit. When the Vicat softening temperature is 60°C or higher, the low-temperature shrinkability of the heat-shrinkable multilayer film is good, and the occurrence of wrinkles when the film is attached to a container can be prevented. When the Vicat softening temperature is 85°C or lower, the low-temperature shrinkability of the heat-shrinkable multilayer film is sufficiently increased, and the occurrence of unshrunk portions when the film is attached to a container can be prevented. The Vicat softening temperature is more preferably 65°C as a lower limit and 80°C as an upper limit. The Vicat softening temperature can be measured by a method in accordance with ISO 306.
[0023] The polystyrene resin preferably has a lower limit of 2 g / 10 min and an upper limit of 15 g / 10 min for the MFR (melt flow rate) at 200° C. If the MFR at 200° C. is less than 2 g / 10 min, it becomes difficult to form a film. If the MFR at 200° C. is more than 15 g / 10 min, the mechanical strength of the film becomes low and it becomes unsuitable for practical use. The more preferred lower limit of the MFR at 200° C. is 4 g / 10 min and the more preferred upper limit is 12 g / 10 min. The MFR can be measured by a method conforming to ISO1133.
[0024] Commercially available polystyrene resins constituting the intermediate layer include, for example, "Clearen" (manufactured by Denki Kagaku Kogyo Co., Ltd.), "Asaflex" (manufactured by Asahi Kasei Chemicals Corporation), "Styrolux" (manufactured by BASF), and "PSJ-Polystyrene" (manufactured by PS Japan Co., Ltd.).
[0025] The lower limit of the styrene component content in the polystyrene resin constituting the intermediate layer is preferably 60% by weight, more preferably 70% by weight, and the upper limit is preferably 90% by weight, more preferably 85% by weight. In addition, when the polystyrene-based resin constituting the intermediate layer is a mixed resin combining a plurality of polystyrene-based resins, the styrene component content in the polystyrene-based resin constituting the intermediate layer is calculated by multiplying the content of each polystyrene-based resin in the mixed resin by the styrene component content of each polystyrene-based resin in the mixed resin and dividing the sum by 100.
[0026] The conjugated diene component content in the polystyrene resin constituting the intermediate layer preferably has a lower limit of 10% by weight, more preferably 15% by weight, and preferably an upper limit of 40% by weight, more preferably 30% by weight. In addition, when the polystyrene resin constituting the intermediate layer is a mixed resin combining a plurality of polystyrene resins, the conjugated diene component content in the polystyrene resin constituting the intermediate layer is calculated by multiplying the content of each polystyrene resin in the mixed resin by the content of the conjugated diene component in each polystyrene resin, and dividing the sum by 100.
[0027] The content of the polystyrene resin in the intermediate layer is preferably 70% by weight in the lower limit and 100% by weight in the upper limit. When the content of the polystyrene resin falls within this range, defects can be confirmed using a polarizing filter. The content of the polystyrene resin in the intermediate layer is more preferably 80% by weight in the lower limit and 95% by weight in the upper limit.
[0028] The polystyrene resin constituting the intermediate layer may be the above polystyrene resin alone or a mixed resin of two or more kinds.
[0029] When two or more of the above polystyrene-based resins are used to form a mixed resin, the difference in Vicat softening temperature between the respective polystyrene-based resins is preferably 2°C or more, more preferably 5°C or more, and is preferably 30°C or less, more preferably 20°C or less.
[0030] The intermediate layer may further contain a polyester resin. The polyester resin may be the same as that constituting the front and back layers. The polyester resin may be the same as that constituting the front and back layers.
[0031] The lower limit of the content of the polyester resin in the intermediate layer is preferably 1% by weight, more preferably 5% by weight, and the upper limit is preferably 30% by weight, more preferably 20% by weight. If the content of the polyester resin is within this range, the retardation value can be reduced, which is preferable.
[0032] The intermediate layer may contain additives such as antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, flame retardants, antibacterial agents, fluorescent whitening agents, and colorants, as necessary.
[0033] (adhesive layer) The heat-shrinkable multilayer film of the present invention may have a structure in which the front and back layers and the intermediate layer are laminated via an adhesive layer.
[0034] The resin constituting the adhesive layer is preferably a polyester-based elastomer, or a modified product thereof, or a mixed resin of a polyester-based resin and a polystyrene-based resin (also referred to as mixed resin (a) in this specification), or a mixed resin of a polystyrene-based resin and a polyester-based elastomer (also referred to as mixed resin (b) in this specification). Such an adhesive layer has high affinity with both the polyester-based resin constituting the front and back layers and the polystyrene-based resin constituting the intermediate layer, and can bond both with high strength. In addition, since it dissolves or swells in a solvent that dissolves the polyester-based resin constituting the front and back layers, the solvent can penetrate into the heat-shrinkable multilayer film during center sealing, and it is possible to prevent interlayer peeling during subsequent heat shrinkage. Furthermore, since the intermediate layer and the front and back layers can be molded by a co-extrusion method, it is also excellent in productivity.
[0035] The polyester elastomer is preferably a saturated polyester elastomer, and more preferably a saturated polyester elastomer containing a polyalkylene ether glycol segment. The saturated polyester elastomer containing the polyalkylene ether glycol segment is preferably, for example, a block copolymer having an aromatic polyester as a hard segment and a polyalkylene ether glycol or an aliphatic polyester as a soft segment, and more preferably a polyester-polyether block copolymer having a polyalkylene ether glycol as a soft segment.
[0036] The polyester polyether block copolymer is preferably one obtained by polycondensing an oligomer obtained by esterification or transesterification using as raw materials (i) an aliphatic and / or alicyclic diol having 2 to 12 carbon atoms, (ii) an aromatic dicarboxylic acid and / or an aliphatic dicarboxylic acid or an alkyl ester thereof, and (iii) a polyalkylene ether glycol.
[0037] As the aliphatic and / or alicyclic diol having 2 to 12 carbon atoms, and the aromatic dicarboxylic acid and / or aliphatic dicarboxylic acid or alkyl ester thereof, those generally used as raw materials for polyesters, particularly polyester elastomers, can be used. Examples of the polyalkylene ether glycol include polyethylene glycol, poly(1,2- and / or 1,3-propylene ether) glycol, poly(tetramethylene ether) glycol, and poly(hexamethylene ether) glycol.
[0038] The number average molecular weight of the polyalkylene ether glycol is preferably 400 at the lower limit, and 6000 at the upper limit. By making the number average molecular weight 400 or more, the block property of the copolymer is increased. By making the number average molecular weight 6000 or less, phase separation in the system is unlikely to occur, and the polymer properties are easily expressed. The number average molecular weight is more preferably 500 at the lower limit, more preferably 3000 at the upper limit, and even more preferably 600 at the lower limit. The number average molecular weight is measured by gel permeation chromatography (GPC). The calibration of the GPC can be carried out, for example, by using a POLYTETRAHYDROFURAN calibration kit (manufactured by POLYMER LABORATORIES, UK).
[0039] The content of the polyalkylene ether glycol component in the polyester polyether block copolymer is preferably 5% by weight at the lower limit and 90% by weight at the upper limit. When the content of the polyalkylene ether glycol component is 5% by weight or more, the block copolymer has excellent flexibility and impact resistance. When the content of the polyalkylene ether glycol component is 90% by weight or less, the block copolymer has excellent hardness and mechanical strength. The more preferred lower limit of the content of the polyalkylene ether glycol component is 30% by weight, the more preferred upper limit is 80% by weight, and the even more preferred lower limit is 55% by weight. The content of the polyalkylene ether glycol component can be calculated based on the chemical shift of hydrogen atoms and their content using nuclear magnetic resonance spectroscopy (NMR).
[0040] The lower limit of the durometer hardness of the polyester elastomer is preferably 10, and the upper limit is preferably 80. By making the durometer hardness 10 or more, the mechanical strength of the adhesive layer is improved. By making the durometer hardness 80 or less, the flexibility and impact resistance of the adhesive layer are improved. The lower limit of the durometer hardness is more preferably 15, and the upper limit is more preferably 70, and the further more preferably 20 and the further more preferably 60. The durometer hardness can be measured by using a durometer type D according to a method in accordance with ISO18517.
[0041] Commercially available products of the polyester elastomer include "Primalloy" (manufactured by Mitsubishi Chemical Corporation), "Pelprene" (manufactured by Toyobo Co., Ltd.), and "Hytrel" (manufactured by DuPont-Toray Co., Ltd.).
[0042] The modified polyester elastomer (hereinafter also referred to as modified polyester elastomer) is the polyester elastomer modified with a modifying agent. The modification reaction for obtaining the modified polyester elastomer is carried out, for example, by reacting the polyester elastomer with an α,β-ethylenically unsaturated carboxylic acid as a modifier. In the modification reaction, it is preferable to use a radical generator.
[0043] In the modification reaction, a graft reaction in which the α,β-ethylenically unsaturated carboxylic acid or its derivative is added to the polyester elastomer mainly occurs, but a decomposition reaction also occurs, resulting in a decrease in the molecular weight of the modified polyester elastomer and a decrease in its melt viscosity. In addition, in the above modification reaction, it is generally considered that other reactions such as ester exchange reactions also occur, and the resulting reaction product generally becomes a composition containing unreacted raw materials, etc. In this case, the preferred lower limit of the content of the modified polyester elastomer in the resulting reaction product is 10% by weight, and the more preferred lower limit is 30% by weight. The closer the content of the modified polyester elastomer is to 100% by weight, the more preferable it is.
[0044] The modification rate (graft amount) of the modified polyester-based elastomer preferably has a lower limit of 0.01% by weight and a higher limit of 10.0% by weight. When the modification rate is 0.01% by weight or more, the affinity between the modified polyester-based elastomer and polyester is high. When the modification rate is 10.0% by weight or less, the decrease in strength due to molecular degradation during modification can be reduced. The more preferred lower limit of the modification rate is 0.03% by weight and a more preferred upper limit is 7.0% by weight, and the even more preferred lower limit is 0.05% by weight and the even more preferred upper limit is 5.0% by weight.
[0045] The modification rate (graft amount) of the modified polyester elastomer can be calculated from the spectrum obtained by H1-NMR measurement according to the following formula (2). The H1-NMR measurement can be performed using an instrument such as "GSX-400" (manufactured by JEOL Ltd.). Graft amount (wt%)=100×[(C÷3×98) / {(A×148÷4)+(B×72÷4)+(C÷3×98)}] (2) In formula (2), A represents the integral value at 7.8 to 8.4 ppm, B represents the integral value at 1.2 to 2.2 ppm, and C represents the integral value at 2.4 to 2.9 ppm.
[0046] The polyester resin constituting the mixed resin of the polyester resin and the polystyrene resin (also referred to as mixed resin (a) in this specification) may be the same as the polyester resin constituting the front and back layers described above, or may be a different one. In particular, it is preferable that the dicarboxylic acid component contains a component derived from terephthalic acid, and the diol component contains components derived from ethylene glycol and 1,4-cyclohexanedimethanol. Such a polyester resin may further contain 0 to 30 mol %, preferably 1 to 25 mol %, more preferably 2 to 20 mol % of a component derived from diethylene glycol.
[0047] When a polybutylene terephthalate resin is used as the polyester resin, in addition to a polybutylene terephthalate resin consisting only of a component derived from terephthalic acid and a component derived from 1,4-butanediol, the polybutylene terephthalate resin may contain a dicarboxylic acid component other than the component derived from terephthalic acid and / or a diol component other than the component derived from 1,4-butanediol. The content of the dicarboxylic acid component other than the component derived from terephthalic acid is preferably 50 mol % or less in 100 mol % of the dicarboxylic acid component. When the content is 50 mol % or less, the heat resistance of the polybutylene terephthalate resin can be maintained. The content of the diol component other than the component derived from 1,4-butanediol is preferably 50 mol % or less in 100 mol % of the diol component.
[0048] In the mixed resin (a), the preferred lower limit of the content of the polyester resin is 5% by weight, and the preferred upper limit is 90% by weight. If the content of the polyester resin is less than 5% by weight, when the overlapping portion is scratched or the perforation is torn after the container is attached, delamination of the heat-shrinkable multilayer film may occur. If the content of the polyester resin is more than 90% by weight, the interlayer strength of the heat-shrinkable multilayer film may decrease, and when the overlapping portion is scratched or the perforation is torn after the container is attached, delamination of the heat-shrinkable multilayer film may occur. The more preferred lower limit of the content of the polyester resin is 10% by weight, the even more preferred lower limit is 25% by weight, the more preferred upper limit is 80% by weight, and the even more preferred upper limit is 75% by weight.
[0049] As the polystyrene resin constituting the mixed resin (a), the same polystyrene resin as that constituting the intermediate layer described above may be used, or a different polystyrene resin may be used. When the polystyrene resin constituting the mixed resin (a) is a styrene-conjugated diene copolymer, the conjugated diene content in 100% by weight of the styrene-conjugated diene copolymer is preferably less than 50% by weight. If the conjugated diene content is 50% by weight or more, when the overlapping portion is scratched or the perforation is torn after installation in the container, delamination of the heat-shrinkable multilayer film may occur.
[0050] In the mixed resin (a), the preferred lower limit of the content of the polystyrene resin is 10% by weight, and the preferred upper limit is 95% by weight. If the content of the polystyrene resin is less than 10% by weight, the interlayer strength of the heat-shrinkable multilayer film may decrease, and when the overlapping portion is scratched or the perforation is torn after the container is attached, the heat-shrinkable multilayer film may delaminate. If the content of the polystyrene resin is more than 95% by weight, the interlayer delamination of the heat-shrinkable multilayer film may occur when the overlapping portion is scratched or the perforation is torn after the container is attached. The more preferred lower limit of the content of the polystyrene resin is 20% by weight, the even more preferred lower limit is 25% by weight, the more preferred upper limit is 90% by weight, and the even more preferred upper limit is 80% by weight.
[0051] The polystyrene-based resin constituting the mixed resin of the above-mentioned polystyrene-based resin and polyester-based elastomer (also referred to as mixed resin (b) in this specification) may be the same as the polystyrene-based resin constituting the intermediate layer described above, or a different one may be used, but it is preferable that the polystyrene-based resin is softer than the polystyrene-based resin constituting the intermediate layer.
[0052] When the polystyrene resin constituting the mixed resin (b) is a styrene-conjugated diene copolymer, the conjugated diene content in 100% by weight of the styrene-conjugated diene copolymer is preferably less than 50% by weight. If the conjugated diene content is 50% by weight or more, peeling may occur from the solvent sealed portion when the container is attached, and when the overlapping portion is scratched or the perforation is torn after the container is attached, interlayer peeling of the heat-shrinkable multilayer film may occur.
[0053] In the mixed resin (b), the preferred lower limit of the content of the polystyrene resin is 10% by weight, and the preferred upper limit is 95% by weight. If the content of the polystyrene resin is less than 10% by weight, when the heat-shrinkable multilayer film is folded strongly, whitening (whitening phenomenon) may occur at the fold, which may impair the appearance. If the content of the polystyrene resin exceeds 95% by weight, the interlayer strength of the heat-shrinkable multilayer film may decrease, and when the overlapping portion is scratched after installation in a container or when the perforation is torn, the heat-shrinkable multilayer film may undergo interlayer delamination. The more preferred lower limit of the content of the polystyrene resin is 20% by weight, and even more preferred lower limit is 25% by weight, and the more preferred upper limit is 90% by weight, and even more preferred upper limit is 85% by weight.
[0054] As the polyester-based elastomer constituting the mixed resin (b), it is preferable to use the same polyester-based elastomer as the polyester-based elastomer constituting the adhesive layer described above.
[0055] The polyester elastomer constituting the mixed resin (b) preferably has a melting point of 120 to 200°C. If the melting point is less than 120°C, the heat resistance of the heat-shrinkable multilayer film decreases, and peeling may occur from the solvent-sealed portion when the film is mounted on a container. If the melting point is more than 200°C, sufficient adhesive strength may not be obtained. The more preferred lower limit of the melting point is 130°C, and the more preferred upper limit is 190°C. The melting point of the polyester elastomer constituting the mixed resin (b) depends on, for example, the copolymerization ratio between the aromatic polyester as the hard segment and the polyalkylene ether glycol as the soft segment, the structure, etc. In particular, the melting point of the polyester elastomer tends to depend on the copolymerization amount of the polyalkylene ether glycol, and the melting point is low when the copolymerization amount of the polyalkylene ether glycol is large, and high when the copolymerization amount of the polyalkylene ether glycol is small.
[0056] In the mixed resin (b), the preferred lower limit of the content of the polyester elastomer is 5% by weight, and the preferred upper limit is 80% by weight. If the content of the polyester elastomer is less than 5% by weight, the interlayer strength of the heat-shrinkable multilayer film may decrease, and when the overlapping portion is scratched or the perforation is torn after installation in the container, the heat-shrinkable multilayer film may delaminate. If the content of the polyester elastomer exceeds 80% by weight, when the heat-shrinkable multilayer film is folded strongly, whitening (whitening phenomenon) may occur at the fold, and the appearance may be impaired. The more preferred lower limit of the content of the polyester elastomer is 10% by weight, and even more preferred lower limit is 15% by weight, and the more preferred upper limit is 75% by weight, and even more preferred upper limit is 70% by weight.
[0057] If necessary, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, etc. may be added to the adhesive layer.
[0058] (Characteristics of heat shrinkable multilayer film) The heat shrinkable multilayer film of the present invention has a retardation lower limit of 0.1 nm and an upper limit of 2900 nm. When the retardation is within the above range, the accuracy of detecting defects in the film can be improved, and defects can be prevented from being overlooked. The lower limit of the retardation is preferably 90 nm, more preferably 100 nm, and the upper limit is preferably 2800 nm, more preferably 2700 nm. The retardation is calculated from the product of the difference in refractive index between the main shrinkage direction and the direction perpendicular thereto in the plane of the film and the film thickness, and specifically, is a value measured using a phase difference measuring device that measures retardation by an optical method (e.g., the KOBRA series manufactured by Oji Scientific Instruments Co., Ltd.).
[0059] The heat shrinkage rate of the heat shrinkable multilayer film of the present invention in the main shrinkage direction (TD direction) when immersed in warm water at 70°C for 10 seconds (hereinafter also referred to as "TD heat shrinkage rate (70°C x 10 seconds)") is preferably 15% in lower limit and 50% in upper limit. When the TD heat shrinkage rate (70°C x 10 seconds) is 15% or more, the shrink finish can be made good. When the TD heat shrinkage rate (70°C x 10 seconds) is 50% or less, natural shrinkage can be suppressed. The TD heat shrinkage rate (70° C.×10 seconds) is more preferably 20% at the lower limit, still more preferably 25% at the lower limit, particularly preferably 30% at the lower limit, more preferably 47% at the upper limit, and still more preferably 45% at the upper limit. The heat shrinkage rate can be calculated by measuring the length after heat shrinking at a predetermined temperature for a predetermined time and calculating the ratio to the length before heat shrinking.
[0060] The heat shrinkage rate of the heat shrinkable multilayer film of the present invention in the main shrinkage direction (TD direction) when immersed in warm water at 100°C for 10 seconds (hereinafter also referred to as "TD heat shrinkage rate (100°C x 10 seconds)") is preferably 60% in lower limit and 85% in upper limit. When the TD heat shrinkage rate (100°C x 10 seconds) is 60% or more, it is possible to prevent wrinkles and the like from occurring during shrinkage.When the TD heat shrinkage rate (100°C x 10 seconds) is 85% or less, it is possible to prevent defects in appearance, such as the label shifting up during shrinkage. The TD heat shrinkage rate (100° C.×10 seconds) is more preferably 65% in the lower limit, still more preferably 70% in the lower limit, more preferably 83% in the upper limit, and still more preferably 82% in the upper limit.
[0061] The heat-shrinkable multilayer film of the present invention has a maximum shrinkage stress of preferably 2.0 MPa (lower limit) and 11 MPa (upper limit) when immersed in 80°C warm water for 30 seconds. If the maximum shrinkage stress is 2.0 MPa or more, the shrink finish when attached to a container can be sufficiently improved. If the maximum shrinkage stress is 11 MPa or less, the interlayer slippage at the center seal portion of the label can be suppressed. In addition, deformation of the container when attached to the container can be suppressed. The more preferable lower limit of the maximum shrinkage stress is 2.5 MPa, and the more preferable upper limit is 10 MPa. The above maximum shrinkage stress refers to the maximum value of the shrinkage stress when the heat-shrinkable multilayer film is immersed in 80° C. warm water for 30 seconds and the shrinkage stress is measured.
[0062] The maximum shrinkage stress can be adjusted, for example, by the stretching conditions (stretching ratio, stretching temperature, etc.) and the Vicat softening temperature of the polystyrene resin used in the intermediate layer. A higher stretching temperature tends to lower the shrinkage stress, whereas a lower stretching temperature tends to increase the shrinkage stress. The stretching temperature needs to be adjusted according to the Vicat softening temperature of the polystyrene resin used in the intermediate layer. Furthermore, if the stretch ratio in the transverse (TD) direction is decreased, the shrinkage stress is decreased, and if the stretch ratio is increased, the shrinkage stress is increased.
[0063] The preferred lower limit of the total thickness of the heat-shrinkable multilayer film of the present invention is 20 μm, and the preferred upper limit is 80 μm. By setting the total thickness of the heat-shrinkable multilayer film within the above range, it becomes economical and easy to handle. In the heat-shrinkable multilayer film of the present invention, the ratio of the thickness of the front and back layers to the thickness of the intermediate layer (thickness of the front and back layers / thickness of the intermediate layer) is preferably 1 / 12 at the lower limit, more preferably 1 / 10 at the lower limit, preferably 1 / 3 at the upper limit, and more preferably 1 / 4 at the upper limit. The thickness of the front and back layers means the thickness of each of the front layer and the back layer.
[0064] The ratio of the thickness of the front and back layers to the total thickness of the heat-shrinkable multilayer film of the present invention is preferably 7% at the lower limit, more preferably 8% at the lower limit, and preferably 18% at the upper limit, more preferably 16% at the upper limit. When the ratio is 7% or more, the solvent resistance and heat resistance of the heat-shrinkable multilayer film can be sufficiently improved. When the ratio is 18% or less, the label can be easily peeled off from the container. For example, when the total thickness of the heat shrinkable multilayer film of the present invention is 40 μm, the lower limit of the thickness of the front and back layers is preferably 2.8 μm, more preferably 3.2 μm, and the upper limit is preferably 7.2 μm, more preferably 6.4 μm.
[0065] The ratio of the thickness of the intermediate layer to the total thickness of the heat-shrinkable multilayer film of the present invention is preferably 60% at the lower limit, more preferably 65% at the lower limit, and preferably 84% at the upper limit, more preferably 82% at the upper limit. When the ratio is 60% or more, the label can be easily peeled off from the container. When the ratio is 84% or less, the heat resistance of the heat-shrinkable multilayer film can be sufficiently improved. For example, when the total thickness of the heat shrinkable multilayer film of the present invention is 40 μm, the lower limit of the thickness of the intermediate layer is preferably 24 μm, the preferred lower limit is 26 μm, the preferred upper limit is 33.6 μm, and the more preferred upper limit is 32.8 μm.
[0066] The ratio of the thickness of the adhesive layer to the total thickness of the heat shrinkable multilayer film of the present invention is preferably 0.5% at the lower limit, more preferably 1% at the lower limit, and more preferably 5% at the upper limit, more preferably 4% at the upper limit. For example, when the total thickness of the heat shrinkable multilayer film of the present invention is 40 μm, the lower limit of the thickness of the adhesive layer is preferably 0.2 μm, more preferably 0.4 μm, and the upper limit is preferably 2 μm, more preferably 1.6 μm.
[0067] The heat-shrinkable multilayer resin film can be produced particularly by a coextrusion-stretching method. In the above-mentioned co-extrusion-stretching method, by changing the extrusion conditions such as resin temperature and cooling temperature, and the stretching conditions such as stretching temperature and stretching ratio (particularly by adjusting the stretching ratio and total thickness), it is possible to adjust the degree of orientation of the resins constituting the laminated front and back layers and the resins constituting the intermediate layer, and therefore the retardation value can be adjusted.
[0068] The use of the heat-shrinkable multilayer film of the present invention is not particularly limited, but since the heat-shrinkable multilayer film of the present invention has high interlayer strength and inhibits delamination when the overlapping portion is scratched or the perforation is torn after attachment to a container, and also has excellent transparency, it is suitably used, for example, as a base film for heat-shrinkable labels to be attached to containers such as PET bottles and metal cans. A heat-shrinkable label made using the heat-shrinkable multilayer film of the present invention is also one aspect of the present invention. Effect of the Invention
[0069] According to the present invention, it is possible to provide a heat-shrinkable multilayer film that makes it easy to detect defects such as scratches and foreign matter present on the film surface and prevents defects such as ink loss after printing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0070] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0071] In the examples and comparative examples, the following raw materials were used. (Polyester resin) Polyester resin A: A polyester resin consisting of a dicarboxylic acid component (component derived from terephthalic acid: 100 mol%) and a diol component (component derived from ethylene glycol: 65 mol%, component derived from diethylene glycol: 20 mol%, component derived from 1,4-cyclohexanedimethanol: 15 mol%) (glass transition temperature: 69°C) Polyester resin B: A polyester resin (melting point: 223°C) consisting of a dicarboxylic acid component (component derived from terephthalic acid: 100 mol%) and a diol component (component derived from 1,4-butanediol: 100 mol%) Polyester resin C: A polyester resin (melting point: 170°C) consisting of a dicarboxylic acid component (component derived from terephthalic acid: 70 mol%, component derived from isophthalic acid: 30 mol%) and a diol component (component derived from 1,4-butanediol: 100 mol%) Polyester resin D: A polyester resin consisting of a dicarboxylic acid component (component derived from terephthalic acid: 100 mol%) and a diol component (component derived from ethylene glycol: 64 mol%, component derived from diethylene glycol: 13 mol%, component derived from 1,4-cyclohexanedimethanol: 23 mol%) (glass transition temperature: 83°C) Polyester resin E: A polyester resin (melting point: 205°C) consisting of a dicarboxylic acid component (component derived from terephthalic acid: 83 mol%, component derived from isophthalic acid: 11 mol%, component derived from adipic acid: 6 mol%) and a diol component (component derived from ethylene glycol: 100 mol%) Polyester resin F: A polyester resin (glass transition temperature: 82°C) consisting of a dicarboxylic acid component (component derived from terephthalic acid: 100 mol%) and a diol component (component relative to ethylene glycol: 68 mol%, component derived from 1,4-cyclohexanedimethanol: 32 mol%).
[0072] (Polystyrene resin) Polystyrene resin A: Styrene-butadiene copolymer (styrene content: 81.3% by weight, butadiene content: 18.7% by weight, Vicat softening temperature: 81°C) Polystyrene resin B: Styrene-butadiene copolymer (styrene content: 79% by weight, butadiene content: 21% by weight, Vicat softening temperature: 59°C) Polystyrene resin C: Styrene-butadiene copolymer (styrene content: 77.7% by weight, butadiene content: 22.3% by weight, Vicat softening temperature: 71°C) Polystyrene resin D: Styrene-butadiene copolymer (styrene content: 72% by weight, butadiene content: 28% by weight, Vicat softening temperature: 76°C) Polystyrene resin E: Styrene-butadiene copolymer (styrene content: 80% by weight, butadiene content: 20% by weight, Vicat softening temperature: 74°C) Polystyrene resin F: Styrene-butadiene copolymer (styrene content: 82% by weight, butadiene content: 18% by weight, Vicat softening temperature: 75°C) Polystyrene resin G: Styrene-butadiene copolymer (styrene content: 75.6% by weight, butadiene content: 24.4% by weight, Vicat softening temperature: 83°C)
[0073] (Polyester elastomer) Polyester elastomer A: Unmodified polyester-polyether block copolymer consisting of polyester as a hard segment and polyether as a soft segment (Toray DuPont, Hytrel 2521, durometer hardness: 55) Polyester-based elastomer B: A modified polyester-polyether block copolymer consisting of polyester as a hard segment and polyether as a soft segment, graft-modified with α,β-ethylenically unsaturated carboxylic acid (Mitsubishi Chemical, Primalloy AP, durometer hardness: 40)
[0074] Example 1 A mixed resin containing 85% by weight of polyester resin A and 15% by weight of polyester resin C was used as the resin constituting the front and back layers. As the resin constituting the intermediate layer, a mixed resin containing 50% by weight of polystyrene resin A and 50% by weight of polystyrene resin B was used. As the resin constituting the adhesive layer, a mixed resin containing 59% by weight of polyester resin A, 10% by weight of polyester resin C, and 31% by weight of polystyrene resin D was used. These resins were put into an extruder with a barrel temperature of 140 to 230 ° C, extruded from a multilayer die at 225 to 230 ° C into a five-layered sheet, and cooled and solidified by a take-up roll at 21 ° C. Next, the film was stretched at a stretch ratio of 6.3 times in a tenter stretching machine with a preheating zone of 100 ° C, a stretching zone of 84 to 89 ° C, and a heat setting zone of 84 ° C, and then wound up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The obtained heat-shrinkable multilayer film had a total thickness of 50 μm and a five-layer structure of a surface layer (7 μm) / adhesive layer (1 μm) / intermediate layer (34 μm) / adhesive layer (1 μm) / back layer (7 μm).
[0075] Example 2 The resin constituting the front and back layers was 100% by weight of polyester resin A. As the resin constituting the intermediate layer, a mixed resin containing 30% by weight of polystyrene resin A and 70% by weight of polystyrene resin C was used. As the resin constituting the adhesive layer, a mixed resin containing 65% by weight of polyester-based elastomer A and 35% by weight of polystyrene-based resin D was used. These resins were put into an extruder with a barrel temperature of 140 to 225 ° C, extruded from a multilayer die at 240 ° C into a five-layered sheet, and cooled and solidified by a take-up roll at 25 ° C. Next, the film was stretched at a stretch ratio of 6.4 times in a tenter stretching machine with a preheating zone of 108 ° C, a stretching zone of 88.5 to 90.5 ° C, and a heat setting zone of 82 ° C, and then wound up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The obtained heat-shrinkable multilayer film had a total thickness of 50 μm and a five-layer structure of a surface layer (7 μm) / adhesive layer (1 μm) / intermediate layer (34 μm) / adhesive layer (1 μm) / back layer (7 μm).
[0076] Example 3 A mixed resin containing 80% by weight of polyester resin A and 20% by weight of polyester resin B was used as the resin constituting the front and back layers. As the resin constituting the intermediate layer, a mixed resin containing 32% by weight of polystyrene-based resin D and 68% by weight of polystyrene-based resin E was used. The resin constituting the adhesive layer was 100% by weight of polyester elastomer B. These resins were put into an extruder with a barrel temperature of 190 to 255 ° C, extruded from a multilayer die at 240 ° C into a five-layered sheet, and cooled and solidified by a take-up roll at 30 ° C. Next, the film was stretched at a stretch ratio of 5.9 times in a tenter stretching machine with a preheating zone of 99 ° C, a stretching zone of 80 to 85 ° C, and a heat fixing zone of 80 ° C, and then wound up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The obtained heat-shrinkable multilayer film had a total thickness of 40 μm and a five-layer structure of a surface layer (5.7 μm) / adhesive layer (0.7 μm) / intermediate layer (27.2 μm) / adhesive layer (0.7 μm) / back layer (5.7 μm).
[0077] Example 4 The resin constituting the front and back layers was 100% by weight of polyester resin A. As the resin constituting the intermediate layer, a mixed resin containing 30% by weight of polystyrene resin A and 70% by weight of polystyrene resin C was used. As the resin constituting the adhesive layer, a mixed resin containing 30% by weight of polyester-based elastomer A and 70% by weight of polystyrene-based resin D was used. These resins were put into an extruder with a barrel temperature of 140 to 225 ° C, extruded from a multilayer die at 240 ° C into a five-layered sheet, and cooled and solidified by a take-up roll at 25 ° C. Next, the film was stretched at a stretch ratio of 6.2 times in a tenter stretching machine with a preheating zone of 106 ° C, a stretching zone of 87 to 90 ° C, and a heat setting zone of 83 ° C, and then wound up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The obtained heat-shrinkable multilayer film had a total thickness of 40 μm and a five-layer structure of a surface layer (5.7 μm) / adhesive layer (0.7 μm) / intermediate layer (27.2 μm) / adhesive layer (0.7 μm) / back layer (5.7 μm).
[0078] Example 5 The resin constituting the front and back layers was 100% by weight of polyester resin A. As the resin constituting the intermediate layer, a mixed resin containing 25.5% by weight of polystyrene resin A, 59.5% by weight of polystyrene resin C, and 15% by weight of polyester resin A was used. As the resin constituting the adhesive layer, a mixed resin containing 30% by weight of polyester-based elastomer A and 70% by weight of polystyrene-based resin D was used. These resins were put into an extruder with a barrel temperature of 140 to 225 ° C, extruded from a multilayer die at 240 ° C into a five-layered sheet, and cooled and solidified by a take-up roll at 25 ° C. Next, the film was stretched at a stretch ratio of 6.2 times in a tenter stretching machine with a preheating zone of 106 ° C, a stretching zone of 87 to 90 ° C, and a heat setting zone of 83 ° C, and then wound up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The obtained heat-shrinkable multilayer film had a total thickness of 40 μm and a five-layer structure of a surface layer (5.7 μm) / adhesive layer (0.7 μm) / intermediate layer (27.2 μm) / adhesive layer (0.7 μm) / back layer (5.7 μm).
[0079] Example 6 The resin constituting the front and back layers was 100% by weight of polyester resin A. As the resin constituting the intermediate layer, a mixed resin containing 30% by weight of polystyrene resin A and 70% by weight of polystyrene resin F was used. As the resin constituting the adhesive layer, a mixed resin containing 60% by weight of polyester-based elastomer B and 40% by weight of polystyrene-based resin D was used. These resins were put into an extruder with a barrel temperature of 170 to 230 ° C, extruded from a multilayer die at 230 ° C into a five-layered sheet, and cooled and solidified by a take-up roll at 28 ° C. Next, the film was stretched at a stretch ratio of 5.8 times in a tenter stretching machine with a preheating zone of 109 ° C, a stretching zone of 81 to 100.5 ° C, and a heat fixing zone of 74 ° C, and then wound up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The obtained heat-shrinkable multilayer film had a total thickness of 40 μm and a five-layer structure of a surface layer (5.7 μm) / adhesive layer (0.7 μm) / intermediate layer (27.2 μm) / adhesive layer (0.7 μm) / back layer (5.7 μm).
[0080] Example 7 The resin constituting the front and back layers was 100% by weight of polyester resin D. As the resin constituting the intermediate layer, a mixed resin containing 80% by weight of polystyrene-based resin G and 20% by weight of polyester-based resin D was used. These resins were put into an extruder with a barrel temperature of 140 to 225°C, extruded from a multilayer die at 240°C into a five-layered sheet, and cooled and solidified by a take-up roll at 25°C. Next, the film was stretched at a stretch ratio of 6.1 times in a tenter stretching machine with a preheating zone of 106°C, a stretching zone of 87 to 90°C, and a heat setting zone of 83°C, and then wound up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The obtained heat-shrinkable multilayer film had a total thickness of 40 μm and a three-layer structure of a surface layer (4.4 μm) / an intermediate layer (31.2 μm) / a back layer (4.4 μm).
[0081] Comparative Example 1 As the resin constituting the front and back layers, a mixed resin containing 50% by weight of polyester-based resin E and 50% by weight of polyester-based resin F was used. As the resin constituting the intermediate layer, a mixed resin containing 50% by weight of polyester-based resin E and 50% by weight of polyester-based resin F was used. These resins were put into an extruder with a barrel temperature of 200 to 210°C, extruded from a multilayer die at 240°C into a five-layered sheet, and cooled and solidified by a take-up roll at 35°C. Next, the film was stretched at a stretch ratio of 6.5 times in a tenter stretching machine with a preheating zone of 88°C, a stretching zone of 85 to 86°C, and a heat setting zone of 86°C, and then wound up by a winding machine to obtain a heat-shrinkable multilayer film in which the direction perpendicular to the main shrinkage direction is MD and the main shrinkage direction is TD. The obtained heat-shrinkable multilayer film had a total thickness of 40 μm and a three-layer structure of a surface layer (6.6 μm) / an intermediate layer (26.8 μm) / a back layer (6.6 μm).
[0082] (evaluation) The heat-shrinkable films obtained in the examples and comparative examples were evaluated by the following methods. The results are shown in Table 1.
[0083] (1) Phase difference (retardation) The heat shrinkable films obtained in the Examples and Comparative Examples were cut into a size of 35 mm in the main shrinkage direction (TD direction) × 35 mm in the direction perpendicular to the main shrinkage direction (MD direction) to prepare a measurement sample. The measurement sample was set in a phase difference measuring device (KOBRA-WR, manufactured by Oji Scientific Instruments) so that the angle defined by this measuring device was 0°, and the retardation at a wavelength of 590 nm at an incident angle of 0° (direction perpendicular to the film surface) was measured.
[0084] (2) Heat shrinkage rate The heat-shrinkable multilayer film was cut to a size of 100 mm in the main shrinkage direction (TD) × 100 mm in the direction perpendicular to the main shrinkage direction (MD), and immersed in 70°C hot water for 10 seconds, after which the heat-shrinkable multilayer film was removed and immediately immersed in tap water for 10 seconds. The length (L) of one side in the TD of this heat-shrinkable multilayer film was measured, and the heat shrinkage in the TD direction was calculated according to the following formula (1). The heat shrinkage after immersion in 80°C hot water for 10 seconds was also measured in the same manner. Heat shrinkage rate (%) = {(100-L) / 100} x 100 (1)
[0085] The heat shrinkage rate was calculated using an average value for a sample number (n) of 3. The heat shrinkage rate was also measured in 100°C hot water in the same manner.
[0086] (3) Check for defects A heat-shrinkable multilayer film measuring 20 cm wide and 100 m long was sandwiched between two 20 cm x 20 cm polarizing films and placed on a white LED light source, with the light source shining on it from below. The polarizing film on top of the heat-shrinkable film was rotated so that the absorption axes of the two polarizing films were perpendicular (crossed Nicols condition), and while rotating, 100 m of the heat-shrinkable film was checked for visible defects and evaluated according to the following criteria. ○: Defects were visible. ×: The interference fringes (rainbow colors) were strong, and the defects were not visible even when the polarization direction was changed.
[0087] [Table 1] [Industrial Applicability]
[0088] According to the present invention, it is possible to provide a heat-shrinkable multilayer film that makes it easy to detect defects such as scratches and foreign matter present on the film surface and prevents defects such as ink loss after printing.
Claims
1. A heat-shrinkable multilayer film having front and back layers containing a polyester resin and an intermediate layer containing a polystyrene resin, The retardation (Re) at a wavelength of 590 nm in a direction perpendicular to the surface of the heat-shrinkable multilayer film is 782 nm or more and 2900 nm or less, The thermal shrinkage rate in the main shrinkage direction when immersed in warm water at 70°C for 10 seconds is 33% or more and 50% or less. A heat-shrinkable multilayer film.
2. The retardation (Re) at a wavelength of 590 nm in a direction perpendicular to the surface of the heat-shrinkable multilayer film is 782 nm or more and less than 1100 nm.
2. The heat-shrinkable multilayer film according to claim 1.
3. The polystyrene resin constituting the intermediate layer contains at least two types of polystyrene resins having a difference in Vicat softening temperature of 2° C. or more and 20° C. or less.
3. The heat-shrinkable multilayer film according to claim 1 or 2.
4. The front and back layers and the intermediate layer are laminated via an adhesive layer, 4. The heat-shrinkable multilayer film according to claim 1, wherein the adhesive layer contains a polyester-based elastomer.
Citation Information
Patent Citations
Film for stretchable label
JP1997330029A
Heat-shrinkable polystyrenic laminated film
JP2005028736A
Heat shrinkable laminated film, molded product using it and container
JP2006159906A
Heat shrinkable multilayer film and heat shrinkable label
JP2008037093A
Heat-shrinkable multilayered film and heat-shrinkable label
JP2011201133A
